Combined metagenomic and archaeobotanical analyses on human dental calculus: A cross-section of lifestyle conditions in a Copper Age population of central Italy. (20th April 2023) - Modi, Alessandra; Attolini, Davide; Zaro, Valentina; Pisaneschi, Lisa; Innocenti, Gabriel; Vai, Stefania; Caramelli, David; Moggi Cecchi, Jacopo; Quagliariello, Andrea; Mariotti Lippi, Marta; Lari, Martina
Abstract: Multidisciplinary analyses on ancient dental calculus revealed the possibility to reconstruct habits and diet of ancient human populations, investigate individual health status, as well as provide information on past environments. In the present study we applied both metagenomic and microscopic analysis on ancient human dental calculus in order to obtain a cross-section of the life conditions in a population of central Italy belonging to the Copper Age culture of Rinaldone (IV millennium BCE). The metagenomic profile suggested an agricultural subsistence and a dietary regimen particularly enriched in complex carbohydrates with low soluble fiber. Even bacterial functional profile seems to indicate an almost exclusive carbohydrates intake that could have favoured the occurrence of nutritional stress in the individuals. Exploring the diversity of the plant food consumed, we detected direct evidence of cereals such as wheat and/or barley, and found signals of the use of leaf vegetables, thus providing additional information on human/environment relationship. The presence of oral pathogens, even if at low abundance (<0.1%), can be related to the high consumption of carbohydrates and finds correspondence with the palaeopathological evidence. In conclusion, starting from very minute amounts of ancient dental calculus, our molecular and microscopic analysis jointly provided complementary data in support of past life condition reconstruction in ancient human populations.